Effects of Stocking Density, Size, and External Stress on Growth and Welfare of African Catfish (Clarias gariepinus Burchell, 1822) in a Commercial RAS - Björn Baßmann; Lisa Hahn; Alexander Rebl; Lisa Carolina Wenzel; Marc-Christopher Hildebrand; Marieke Verleih; Harry Wilhelm Palm (Fishes, 2023)
The effects of semi-intensive (100 kg m−3), intensive (200 kg m−3), and super-intensive (400 kg m−3) stocking densities on the growth and welfare of African catfish (Clarias gariepinus) were investigated under commercial production conditions. Plasma cortisol, glucose, and selected transcripts following a stress challenge, lactate, as well as skin lesions, were analyzed at regular intervals (from 12 g juveniles to 1.5–2.0 kg). The fish grew well, but after 23 weeks, the semi-intensively stocked fish had a mean final weight of 1830.5 g, significantly higher than the super-intensively stocked fish with 1615.4 g, and considerably higher than the intensively stocked fish with 1664.8 g (p > 0.05). Cortisol and glucose responses significantly differed between stressed and unstressed fish, but not between treatment groups. An unforeseen external stressor (nearby demolition noise) caused stress responses among all treatment groups, but was similarly coped with. Mortality ranged between 3.8–9.2%. In the juveniles, skin lesions were reduced under intensive or super-intensive densities, with the least under semi-intensive densities in outgrown fish. Expression profiles of 22 genes were compared in the spleen at semi-intensive and super-intensive densities. The transcript concentrations of most genes remained unchanged, except for slc39a8 and mtf1, which were significantly downregulated in stressed catfish under semi-intensive conditions. We demonstrated that African catfish growth performance and welfare depend on age and stocking density, also reacting to demolition noise. This supports farm management to optimize stocking densities during the grow-out of African catfish in RAS and suggests avoiding external stress.